Automatic Satay Grill Using 5 Volt Stepper Motor for Home Business - Prayoga, Dimas Dwi; Anshory, Izza; Wicaksono, Arief; Syahrorini, Syamsudduha (Buletin Ilmiah Sarjana Teknik Elektro, 2024)
Increased consumer demand for satay dishes as one of the traditional culinary demands innovation in the manufacturing process to improve efficiency and consistency. This research aims to design and implement a dc stepper motor-based automatic satay grill system as a solution for small businesses. This system uses a DC stepper motor as the main component, using an Arduino UNO microcontroller programmed to regulate the temperature and automatic rotation of the satay. The measurement uses a built-in LM35 temperature sensor to monitor the temperature during grilling to ensure optimal doneness. In addition, the system is equipped with an interface using an LCD screen connected to the Arduino UNO microcontroller to monitor the temperature and condition of the satay grill, allowing the user to easily set the grilling parameters according to preference. During testing of the prototype, results showed that this automatic satay grill system is capable of producing satay with uniform doneness and meeting quality standards. In addition, time and labor efficiency improved, making a positive contribution to the productivity of small and medium enterprises. Overall, this development provides an innovative and effective solution in improving the satay production process, positively impacting traditional culinary businesses.